Piriformospora indica Enhances Rice Blast Resistance and Plant Growth - Manegdebwaoga Arthur Fabrice Kabore; Guanpeng Huang; Changqing Feng; Shuhong Wu; Jiayi Guo; Guofeng Wu; Yiqiong Sun; Samuel Tareke Woldegiorgis; Yufang Ai; Lina Zhang; Wei Liu; Huaqin He (Agronomy)
Rice blast disease, caused by Magnaporthe oryzae (M. oryzae), is a significant threat to global rice production. Conventional methods for disease management face limitations, emphasizing the importance of sustainable alternatives. In this study, two rice cultivars with different blast resistant abilities, the susceptible variety CO39 and the resistant variety Pi4b, were used as materials to study the effects of Piriformospora indica (Pi) on the resistance to M. oryzae infection and rice growth. The in vitro tests revealed no direct antagonistic interaction between Pi and M. oryzae. However, the in vivo experiments showed that Pi promoted plant growth by increasing root and shoot length, chlorophyll content, and nitrogen uptake, particularly in CO39 during pathogen infection. Pi inoculation also significantly reduced disease severity, which was indicated by smaller lesion areas and shorter lesion lengths in both cultivars but a more pronounced effect in CO39. This occurred due to the decreasing levels of MDA and the modulating activity of antioxidant enzymes in Pi-inoculated rice plants. At the early stage of M. oryzae infection, the expression of the ethylene signaling gene OsEIN2 and the gibberellin biosynthesis gene OsGA20ox1 in Pi-inoculated CO39 decreased but significantly increased in both rice cultivars at the later stage. The reverse was found for the pathogenesis-related (PR) genes OsPR10 and OsPBZ1 and the blast-resistant genes OsBRG1, OsBRG2, and OsBRW1, suggesting early growth suppression for rice resilience to blast followed by a later shift back to growth. Meanwhile, Pi inoculation increased OsCesA9 expression in rice to strengthen cell walls and establish the primary defense barrier against M. oryzae and upregulated the expression of OsNPR1 without a significant difference in CO39 but downregulated it in Pi4b to activate PR genes to enhance plant resistance. In summary, these results underscore the potential of Pi as a sustainable biological control agent for rice blast disease, which is particularly beneficial for blast-susceptible rice cultivars.